Pengaruh Perekonomian Masyarakat dengan Adanya Perusahaan Perkebunan Kelapa Sawit di Kabupaten Banyuasin Sumatera Selatan - Yustika, Gaung Perwira; Septiani (Haka Vyza Media, 2024)
This research uses a qualitative research approach, namely by using interviews or direct interviews with community members, both oil palm farmers and non-oil palm farmers. This research uses qualitative descriptive methods, especially direct field research. Village governments, oil palm farmers, entrepreneurs, traders and ordinary citizens are the data sources in this research. In addition, secondary data obtained from the village office was also used in this research. The findings of this research indicate that oil palm farming is very important for the economy of the people of Banyuasin Regency. Therefore, it is very important for oil palm farmers to contribute significantly to the empowerment of oil palm plantations in order to improve the quality of life of rural communities, because oil palm plantations are very important for the existence of these communities. The main concern of this research is the influence of palm oil production on the income of the people of Banyuasin Regency. Based on the findings of this research, palm oil production has a significant influence on people's income. Role indicators include the following: consistent employment and income for the community; improving children's educational lives improves; agricultural zakat expenditure; please help each other; increasing individual participation in the Umrah and Hajj; and intention to work which is exemplified by hard work, sincere work and smart work.